Tiktok Video: An Innovative Platform in Teaching Speaking Skill - Tjiangrayudi B Alfaron; Aminah Suriaman; Afrillia Anggreni; Rofiqoh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
There were several challenges in speaking faced by students of SMP Negeri 1 Palu. When the students talk, they often had short pause because they were effortful to decide and generate their ideas. Furthermore, the students were not confident to speak up in front of the class because they did not know how to pronounce the word correctly. Thus, the researchers tried to answer the problems above by using Tiktok stich video. The objective of this research was to prove that the use of Tiktok could improve students' speaking skills of the eight grade of SMP Negeri 1 Palu. Quasi-experimental research design was implemented including pre-test, treatment, and post-test. The population is 349 students. The researchers used purposive sampling to select the sample, VIIID as control group and VIIIG as Experimental group. After collecting and analyzing the data statistically, in pre-test, the mean score of experimental class was 41.88 and on the other hand, the mean score of control class was 52.81. Furthermore, in the post- test, the mean score of experimental class is 75.62 while the mean score of control class is 64.38. This result indicates that Tiktok stitch video improve students speaking skill in fluency and accuracy. Thus, it can be interpreted that teaching using Tiktok stitch video effectively increase students' speaking skill of the eighth grade students of SMP Negeri 1 Palu. The conclusion implies that Tiktok stich video is an innovative and valuable platform that carried out by the teacher and the students in teaching and learning English speaking